Superiority of Female Characters in the Novel Kenanga and Tempurung by Oka Rusmini - Alvionita, Frisca Nabila; Hartono, Hartono (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research describes the form of superiority of female characters and the contribution of superior characters to the women's movement in the Novel Kenanga and Tempurung by Oka Rusmini. Data was collected using reading techniques and note-taking techniques. Data were analyzed using psychoanalytic feminist literary criticism theory. As a result, the form of superiority of the female characters in the novel Kenanga with its character named Kenanga and the novel Tempurung by Oka Rusmini, namely Bu Barla and Saring, has the superiority of responsibility, hardworking, caring, intelligent, patient. The background to the emergence of superiority in the character Kenanga is found in the Novel Kenanga. The contribution for women is the desire of female writers to change perceptions in society which consider women as inferior human beings. The author wants there to be a change in perceptions in society so that the levels of women and men are considered the same.